Prevalência do tabagismo e seus fatores associados entre trabalhadores do Sistema Único de Saúde em Belo Horizonte - Luiz Fabio Machado Barbosa (2014)
Smoking in health care professionals can impact not only their own health status, but also their professional assistance. Health care providers should set a model for others, and then smoking can undermine their professional credit and also their delivery ofsmoking cessation programs because they tend to address smoking issues less frequently. In developing countries, smoking prevalence in health workers tends to be similar or even higher compared to the general population. In addition, most public health systems require teamwork. However, little is known about smoking in Brazilian healthcare workers as a whole labour category. The aim of this study is to identify the prevalence of, and factors related to, smoking among health workers of the National Health System in Belo Horizonte, Minas Gerais. A cross-sectional study was conducted in 2008/2009 with a stratified sample. Data about socio-demographic, health, employment and work characteristics were analyzed. Participants were defined as current smokers (those who had smoked at least 100 cigarettes over their lifetime and still smoking at the time of the interview), ex-smokers (those who reported that had smoked at least 100 cigarettes over their lifetime but did not smoke at the time of the interview) and nonsmokers(those who had never smoked). This variable was dichotomized, being defined as smokers who reported they were current smokers and non-smokers who are former smokers or nonsmokers. To analyze the association between variables, we used bivariate and multivariate logistic regression and also estimate crude and adjusted odds ratio at alevel of significance of 5% for inclusion in the final model. The overall prevalence of smoking was 15.7% (13.1% among females and 22.2% among males). Out of a total of 1.808 participants in the study, 71.6% were female; with mean age of 40.8 years and 54.2% had high-school, technical or incomplete university education. It was observed that 23.0% occupied administrative positions or other general services and the mean income was R$ 1932.12. According to workplace conditions, 50.5% felt reasonable the relationship between requirements and available resources; workplace conditions were reported as poor by 35.2% of participants; highly physically demanding tasks were reportedby 67.4% of the sample and 74.7% described your work as highly emotional demanding. Reasonable relationship between requirements and available resources remained negatively correlated to smoking in the final model. The variables that remained positively associated with smoking in the final model were: being male; administrative and other general services workers, professionals involved in monitoring, community health workers, technical mid-level workers and were included nurses and practical nurses (p<.05). Concluding, the results showed socio-demographic, health, employment and work characteristics of the target population that should be emphasized by intervention programs for prevention and smoking cessation.